ANALYSIS OF NURSES’ JOB BURNOUT AND COPING STRATEGIES - Маркусова, Тетяна; Стаханська, Ольга; Бойцанюк, Світлана (SWorldJournal, 2023)
In recent years, nursing has come to be considered a high-risk and high-pressure profession The aim of this study is to investigate the level of burnout of clinical nurses.To study the syndrome of emotional burnout, we used the Questionnaire of burnout M